Repeated low-dose rituximab treatment based on the assessment of circulating B cells in patients with refractory myasthenia gravis. (September 2019) - Choi, Kyomin; Hong, Yoon-Ho; Ahn, So-Hyun; Baek, Seol-Hee; Kim, Jun-Soon; Shin, Je-Young; Sung, Jung-Joon
Background: The objective of this study was to evaluate the efficacy and safety of repeated low-dose rituximab treatment guided by monitoring circulating CD19+ B cells in patients with refractory myasthenia gravis (MG). Methods: Patients with refractory MG who had received rituximab treatment at two teaching hospitals between September 2013 and January 2017 were reviewed retrospectively. The treatment protocol consisted of an induction treatment with low-dose rituximab (375 mg/m 2 twice with a 2-week interval), followed by retreatment (375 mg/m 2 once). Retreatment was based on either circulating CD19+ B-cell repopulation or clinical relapse. Outcome measures included the MG Foundation of America (MGFA) clinical classification and postintervention status, prednisolone dose, CD19+ B-cell counts, clinical relapse, and adverse effects. Results: Of 17 patients, 11 (65%) achieved the primary endpoint, defined as the minimal manifestation or better status with prednisolone ⩽5 mg/day, after median 7.6 months (range, 2–17 months) following rituximab treatment. Over a median follow up of 24 months (range, 7–49 months), a total of 30 retreatments were undertaken due to clinical relapse without B-cell repopulation ( n = 6), on the basis of B-cell repopulation alone ( n = 16) and both ( n = 8). B-cell recovery appeared to be in parallel with clinical relapse on the group level, although the individual-level association appeared to be modest, with B-cell repopulation observed only at 57% (8/14) of clinical relapses. Conclusions: The repeated low-dose rituximab treatment based on the assessment of circulating B-cell depletion could be a cost-effective therapeutic option for refractory MG. Further studies are needed to verify the potentially better cost-effectiveness of low-dose rituximab, and to identify biomarkers that help optimize treatment in MG patients.